Ultralow-temperature sintered ceramic material as well as preparation method and application thereof
By sintering NaAg1-xBix/3MoO4 ceramic material between 400°C and 535°C, the problem of high sintering temperature in the prior art is solved, and ceramic materials with excellent dielectric properties are prepared under ultra-low temperature conditions, which is suitable for industrial production. And broaden the application boundaries.
Patent Information
- Application Number
- CN202411447477.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The sintering temperature of existing microwave dielectric ceramic materials is relatively high, which is difficult to meet the requirements of ultra-low temperature co-fired ceramic technology, which limits its potential in high-end applications.
Using NaAg1-xBix/3MoO4 ceramic material, the traditional solid phase method is used to sinter it between 400°C and 535°C, and the appropriate amount of Bi3+ is used to replace and control the sintering temperature to form a spinel structure of Fd-3m (227) to achieve dielectric Excellent performance of performance.
Ceramic materials with dielectric constant εr of 6.99~7.55, Q×f is 8586~18867GHz, and τf is -82.42ppm/℃~-88.07ppm/℃ are prepared under ultra-low temperature conditions, which shortens the preparation cycle and is suitable for industrial production. The denseness and dielectric properties of the material are significantly improved.
Smart Images

Figure CN119320276A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of microwave dielectric ceramic materials, and in particular relates to an ultra-low temperature sintered ceramic material and a preparation method and application thereof. Background Art
[0002] With the rapid evolution of communication technology, the design standards of microwave components have become increasingly stringent, and miniaturization, lightness, high-frequency response, and low energy consumption have become key pursuits. Multilayer chip components have not only greatly reduced the size of the equipment and reduced costs through a highly integrated strategy, but also demonstrated excellent performance in the low-temperature co-firing process by integrating low-loss metal electrodes. Today, the industry is actively exploring new frontiers in ULTCC (ultra-low temperature co-fired ceramic) technology, striving to sinter at lower temperatures, further reduce energy consumption, and expand the application boundaries of materials. Breakthroughs in ULTCC technology will lead microwave components to develop in a more compact, efficient, and energy-saving direction, laying a solid foundation for the next leap in communication technology.
[0003] In the current field of microwave dielectric ceramic material preparation, although significant progress has been made, traditional methods are often accompanied by high sintering temperatures. Taking the Chinese patent application number 202110622929.8 as an example, this patent introduces Co 2+ Ion replacement Ba 2+ , and successfully prepared Ba with relatively excellent dielectric properties at a higher sintering temperature of 900-950℃ 3-x Co x (VO4)2 ceramics, the product of dielectric constant and quality factor (Q×f) ranges from 25318 GHz to 54063 GHz, and the resonant frequency temperature coefficient (τ f ) is controlled between +14.5ppm / ℃ and +23.8ppm / ℃. Nevertheless, this sintering temperature still does not meet the stringent standards of ULTCC (ultra-low temperature co-fired ceramic) technology, limiting its potential in some high-end applications.
[0004] Therefore, the purpose of the present application is to provide an ultra-low temperature sintered ceramic material having excellent dielectric properties, and the ceramic material can be prepared under ultra-low temperature sintering conditions. Summary of the invention
[0005] Based on the above, the present invention aims to provide an ultra-low temperature sintered ceramic material and its preparation method and application, the ceramic material exhibits excellent dielectric properties, Q×f is 8586~18867GHz, τ f -82.42ppm / ℃~-88.07ppm / ℃, dielectric constant ε rIn addition, the ultra-low temperature sintered ceramic material of the present application is prepared by a traditional solid phase method, with a low sintering temperature and no need for adhesives, a short preparation cycle, and is suitable for industrial production.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention provides an ultra-low temperature sintered ceramic material, characterized in that the composition expression of the ceramic material is NaAg 1-x Bi x / 3 MoO4, x is 0.06 to 0.24. The ceramic material includes a spinel structure with a space group of Fd-3m (227). For example, x can be 0.06, 0.12, 0.18 or 0.24.
[0008] In some feasible examples, the average grain size of the ceramic material is 4-5 μm.
[0009] In some feasible examples, the dielectric constant ε of the ceramic material is r It is 6.99 to 7.55, for example, 6.99 to 7.15, 7.15 to 7.25, 7.25 to 7.35 or 7.35 to 7.55.
[0010] In some feasible examples, the Q×f of the ceramic material is 8586-18867 GHz, such as 8586-12000 GHz, 12000-16000 GHz, or 16000-18867 GHz.
[0011] In some feasible examples, the temperature drift coefficient τ of the ceramic material is f It is -82.42ppm / °C to -88.07ppm / °C, for example, -82.42ppm / °C to -84ppm / °C, -84ppm / °C to -86ppm / °C or -86ppm / °C to -88.07ppm / °C.
[0012] The density of the ceramic material is 3.50-4.69 g / cm 3 , for example 3.50~4.0g / cm 3 4.0~4.4g / cm 3 or 4.4~4.69g / cm 3 .
[0013] In some feasible examples, the Na source in the ceramic material is a carbonate of Na, the Ag source is a carbonate of Ag, the Bi source is an oxide of Bi, and the Mo source is an oxide of Mo. Preferably, the Na source is Na2CO3, the Ag source is Ag2CO3, the Bi source is Bi2O3, and the Mo source is MoO3.
[0014] In some feasible examples, the purity of the Na source, Ag source, Bi source and Mo source in the ceramic material is greater than or equal to 99.0%. Preferably, the purity of the Na source is greater than or equal to 99.9%, the purity of the Ag source is greater than or equal to 99.5%, the purity of the Bi source is greater than or equal to 99.0%, and the purity of the Mo source is greater than or equal to 99.5%.
[0015] The second aspect of the present invention provides a method for preparing the ultra-low temperature sintered ceramic material, comprising the following steps:
[0016] 1) According to NaAg 1-x Bi x / 3 The Na source, Ag source, Bi source and Mo source are weighed and mixed thoroughly to obtain a raw material powder in a stoichiometric ratio of MoO4;
[0017] Preferably, in the step 1), the particle sizes of the Na source, Ag source, Bi source and Mo source are all 360-400 meshes.
[0018] 2) Add deionized water to the mixed raw material powder in step 1), let it stand, perform a first ball milling, a first drying, a first screening and then pre-calcination, and then perform a second ball milling, a second drying, and a second screening to obtain a pretreated raw material powder.
[0019] Preferably, in step 2), deionized water is added so that the raw material powder can be fully dispersed in the water, and then allowed to stand for 15 to 18 hours;
[0020] More preferably, the ball milling speed of the first ball milling is 300-400 rpm, and the ball milling time is 21-24 h;
[0021] More preferably, the first drying temperature is 80-95° C., and the drying time is 3-24 hours. The drying time is based on the powder weight not decreasing, and excess moisture is removed to facilitate subsequent grinding and granulation.
[0022] More preferably, the mesh number of the first screening is 40-80 meshes, such as 40, 50, 60, 70 or 80 meshes. The mesh number of the second screening is 80-110 meshes, such as 80, 90, 100 or 110 meshes.
[0023] More preferably, the pre-calcination is heating to 325-375°C at a heating rate of 2-5°C / min and pre-calcining for 3.5-4 hours. The temperature may be 325, 350 or 375°C.
[0024] More preferably, the conditions for the second ball milling are the same as those for the first ball milling, and the conditions for the second drying are the same as those for the first drying.
[0025] The pretreated raw material powder obtained in step 2) is pure and uniform, which is conducive to subsequent sintering.
[0026] 3) The pre-treated powders in step 2) are mixed and pressed into shape, and then sintered at a low temperature to obtain an ultra-low temperature sintered ceramic material.
[0027] Preferably, the ceramic green body is pressed under a pressure of 1 to 3 bar, and the ceramic green body is continuously sintered for 3.5 to 4 hours at a temperature of 400 to 535°C to obtain an ultra-low temperature sintered ceramic material. The temperature may be 400, 425, 450, 475, 500, 525 or 535°C.
[0028] More preferably, the ceramic green body is a cylindrical block with a diameter of 10 to 12 mm and a height of 4 to 6 mm;
[0029] More preferably, before sintering, the ceramic green body is left to stand for 8 to 10 hours to discharge excess water.
[0030] This application has at least the following beneficial technical effects:
[0031] (1) The present invention provides an ultra-low temperature sintered ceramic material with low dielectric constant and low loss, the composition expression of which is NaAg 1-x Bi x / 3 MoO4, where x is 0.06 to 0.24, the ceramic material of this composition has ε r is 6.99~7.55, Q×f is 8586~18867GHz, τ f The temperature is -82.42ppm / ℃~-88.07ppm / ℃, and the density is 3.50~4.69g / cm 3 .
[0032] (2) The preparation method of the present invention sets the sintering temperature range between 400°C and 535°C. This low temperature range significantly shortens the preparation cycle, making the entire production process faster, and the prepared ceramic material has good densification and excellent dielectric properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The present invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.
[0034] Figure 1 NaAg 1-x Bi x / 3 XRD patterns of MoO4 (x=0.06, 0.12, 0.18, 0.24) ceramic materials sintered at 450℃;
[0035] Figure 2 is NaAg in Example 1 1-x Bix / 3 Scanning electron microscope (SEM) image of MoO4 (x = 0.06) ceramic material at 450 °C;
[0036] Figure 3 NaAg at 400~535℃ sintering temperature 1-x Bi x / 3 Density variation diagram of MoO4 (x=0.06, 0.12, 0.18, 0.24) ceramic materials. DETAILED DESCRIPTION
[0037] The present invention will be described in detail below by specific examples. These examples are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art.
[0038] The ε in this application r , Q×f is measured by network analyzer in combination with Hakki-Coleman dielectric resonant cavity method. τ f The test was conducted at 20°C to 80°C. In addition, the test methods in the following examples are all conventional methods unless otherwise specified. The reagents and materials used can be obtained through commercial channels unless otherwise specified.
[0039] Example 1
[0040] Preparation of NaAg 1-x Bi x / 3 MoO4(x=0.06) ceramic material
[0041] 1) Raw material preparation and mixing
[0042] Sodium carbonate (Na2CO3) powder with a purity of 99.9%, silver carbonate (Ag2CO3) powder with a purity of 99.95%, bismuth trioxide (Bi2O3) powder with a purity of 99.0%, and molybdenum trioxide (MoO3) powder with a purity of 99.5%, all of which have a mesh size of about 360 to 400 meshes.
[0043] The total mass is 120g, according to the chemical formula NaAg 1-x Bi x / 3 The ratio of MoO4, accurately weigh these powders and mix them evenly to obtain the raw material powder and place it in a ball mill.
[0044] 2) Wet grinding and pre-burning
[0045] Deionized water was added to the ball mill as a medium and allowed to stand for 16 hours to ensure adequate wetting.
[0046] After exhausting the gas in the tank, the first ball milling treatment was performed for 22 hours to obtain a uniform slurry.
[0047] The slurry was poured out and dried for the first time in an environment of 90° C., and then sieved through a 50-mesh screen.
[0048] The sieved powder was heated to 350°C in a muffle furnace at a heating rate of 2.5°C / min and pre-calcined for 4 hours.
[0049] After the pre-calcination, the powder was mixed with deionized water again and ball-milled for a second time for 22 hours, followed by a second drying in a 90° C. environment, and then sieved through a 100-mesh sieve to obtain a pretreated raw material powder.
[0050] 3) Molding and sintering
[0051] The pretreated raw material powder was pressed into cylindrical blocks of specific size (diameter 11.8 mm, height 5.5 mm) at a pressure of 2 bar.
[0052] Allow the pressed cylindrical blocks to rest for 9 hours to drain excess surface moisture.
[0053] The block is placed in a sintering furnace, heated to 450°C at a heating rate of 2.5°C / min, and sintered at this temperature for 4 hours to finally obtain the desired ultra-low temperature sintered ceramic material.
[0054] Through the above steps, NaAg 0.94 Bi 0.02 MoO4 ceramic material.
[0055] Depend on Figure 1 As shown in Figure 2, the XRD diffraction peaks are consistent with the phase of NaAgMoO4 (PDF#04-008-4322), which confirms the formation of NaAg with space group Fd-3m (227). 0.94 Bi 0.02 MoO4 spinel structure.
[0056] Figure 2 This is the SEM image of the ceramic in this example. It can be seen that the sample is sintered densely and the average grain size is 4 to 5 μm.
[0057] The ε of the microwave dielectric ceramic material prepared in this example r , Q×f value and τ f They are 6.99, 10971GHz, and -86.49ppm / ℃ respectively.
[0058] Example 2
[0059] Each step is basically the same as in Example 1, except that the chemical formula ratio and weighing are different. In this example, NaAg 1-x Bi x / 3MoO4 (x=0.12) was weighed.
[0060] Depend on Figure 1 As shown in Figure 2, the XRD diffraction peaks are consistent with the phase of NaAgMoO4 (PDF#04-008-4322), which confirms the formation of NaAg with space group Fd-3m (227). 0.88 Bi 0.04 MoO4 spinel structure.
[0061] The ε of the microwave dielectric ceramic material prepared in this example r , Q×f value and τ f They are 7.092, 15950GHz, and -88.07ppm / ℃ respectively.
[0062] Example 3
[0063] Each step is basically the same as in Example 1, except that the chemical formula ratio and weighing are different. In this example, NaAg 1-x Bi x / 3MoO4 (x=0.18) was weighed.
[0064] Depend on Figure 1 As shown in Figure 2, the XRD diffraction peaks are consistent with the phase of NaAgMoO4 (PDF#04-008-4322), which confirms the formation of NaAg with space group Fd-3m (227). 0.82 Bi 0.06 MoO4 spinel structure.
[0065] The ε of the microwave dielectric ceramic material prepared in this example r , Q×f value and τ f They are 7.38, 18867 GHz, and -84.83 ppm / ℃ respectively.
[0066] Example 4
[0067] Each step is basically the same as in Example 1, except that the chemical formula ratio and weighing are different. In this example, NaAg 1-x Bi x / 3MoO4 (x=0.24) was weighed.
[0068] Depend on Figure 1 As shown in Figure 2, the XRD diffraction peaks are consistent with the phase of NaAgMoO4 (PDF#04-008-4322), which confirms the formation of NaAg with space group Fd-3m (227). 0.76 Bi 0.08 MoO4 spinel structure.
[0069] The ε of the microwave dielectric ceramic material prepared in this example r , Q×f value and τ f They are 7.55, 8586 GHz, and -82.42 ppm / ℃ respectively.
[0070] Embodiments 5 to 10
[0071] Examples 5 to 10 are substantially the same as Example 1, except that the sintering temperatures in step 2) are 400° C., 425° C., 475° C., 500° C., 525° C. and 535° C., respectively.
[0072] Examples 11 to 16
[0073] Examples 11 to 16 are substantially the same as Example 2, except that the sintering temperatures in step 2) are 400°C, 425°C, 475°C, 500°C, 525°C and 535°C, respectively.
[0074] Examples 17 to 22
[0075] Examples 17 to 22 are substantially the same as Example 3, except that the sintering temperatures in step 2) are 400°C, 425°C, 475°C, 500°C, 525°C and 535°C, respectively.
[0076] Embodiments 23 to 28
[0077] Examples 23 to 28 are substantially the same as Example 4, except that the sintering temperatures in step 2) are 400°C, 425°C, 475°C, 500°C, 525°C and 535°C, respectively.
[0078] like Figure 1 As shown in (a), the NaAg prepared in Examples 1 to 4 1-x Bi x / 3 XRD patterns of MoO4 (x=0.06, 0.12, 0.18, 0.24) ceramics show that NaAg 1-x Bi x / 3 Most of the diffraction peaks in MoO4 are consistent with the phase of NaAgMoO4 (PDF#04-008-4322), which indicates that NaAg with a space group of Fd-3m (227) and a spinel structure has been synthesized. 1-x Bi x / 3 The crystal phase of MoO4, a few diffraction peaks and Na 0.5 Bi 0.5 MoO4 (PDF#04-005-8490), indicating that a small amount of secondary phase was formed during the synthesis.
[0079] In addition, plum blossom The marked diffraction peaks are other unknown crystal phases. Excessive presence of secondary phases will affect the air tightness of the ceramic sample and thus affect the dielectric loss. On the other hand, Figure 1 (b) The (311) diffraction peak follows the Bi 3+ The content of Bi increases and gradually shifts to the right. 3+ The ionic radius is smaller than that of Ag + The ionic radius further explains that Bi 3+ With Ag + Soluble to form solid solution NaAg 1-x Bi x / 3 MoO4 ceramics.
[0080] exist Figure 3 The NaAg prepared in Examples 1 to 28 is shown in 1-x Bi x / 3 The apparent density variation trend of MoO4 ceramics. The specific density data are shown in Table 1.
[0081] Table 1
[0082]
[0083] Depend on Figure 3 As shown in Table 1, when the sintering temperature is 450℃ and x=0.18, the sample density reaches the highest, which means that the dielectric loss is low. 0.82 Bi 0.06 The density of MoO4 reaches the highest level at 4.69 g / cm 3 This indicates that the appropriate amount of Bi 3+ It can promote the densification of ceramics.
[0084] The present invention first discovered that by controlling the temperature and Bi 3+ The appropriate amount of substitution promotes the densification of ceramics. The significant sign of the densification process is the significant reduction in the number of pores and the moderate increase in grain size. The synergistic effect of the two greatly improves the apparent density of the sample. Specifically, the reduction of pores means that the internal space of the material is more effectively filled, reducing the scattering of sound waves and energy loss; and the moderate growth of grains enhances the transmission efficiency of sound waves without sacrificing the toughness of the material, making the material show excellent Q×f value in high-frequency applications. Among them, NaAg 1-x Bi x / 3MoO4, when x is 0.18, the ε r =7.55, Q×f=18867GHz, τ f =-84.8ppm / ℃, and density is 4.69g / cm 3 .
[0085] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. An ultra-low temperature sintered ceramic material, characterized in that: The composition expression of the ceramic material is NaAg 1-x Bi x / 3MoO4, x is 0.06 to 0.24; The ceramic material includes a spinel structure having a space group of Fd-3m(227).
2. The ultra-low temperature sintered ceramic material according to claim 1, characterized in that: The average grain size of the ceramic material is 4 to 5 μm; And / or, the dielectric constant ε of the ceramic material r 6.99~7.55; and / or, the Q×f of the ceramic material is 8586 to 18867 GHz; And / or, the temperature drift coefficient τ of the ceramic material f -82.42ppm / ℃~-88.07ppm / ℃; And / or, the density of the ceramic material is 3.50-4.69 g / cm 3 .
3. The ultra-low temperature sintered ceramic material according to claim 2, characterized in that: The Na source in the ceramic material is Na carbonate, the Ag source is Ag carbonate, the Bi source is Bi oxide, and the Mo source is Mo oxide; And / or, the purity of the Na source, Ag source, Bi source and Mo source in the ceramic material is greater than or equal to 99.0%.
4. The ultra-low temperature sintered ceramic material according to claim 3, characterized in that: The Na source is Na2CO3, the Ag source is Ag2CO3, the Bi source is Bi2O3, and the Mo source is MoO3; And / or, the purity of the Na source is greater than or equal to 99.9%, the purity of the Ag source is greater than or equal to 99.5%, the purity of the Bi source is greater than or equal to 99.0%, and the purity of the Mo source is greater than or equal to 99.5%.
5. The method for preparing the ultra-low temperature sintered ceramic material according to any one of claims 1 to 4, comprising the following steps: 1) According to NaAg 1-x Bi x / 3 The Na source, Ag source, Bi source and Mo source are weighed and mixed thoroughly to obtain a raw material powder in a stoichiometric ratio of MoO4; 2) adding deionized water to the mixed raw material powder in step 1), allowing to stand, subjecting the mixed raw material powder to a first ball milling, a first drying, a first sieving, and then pre-calcining, and subjecting the mixed raw material powder to a second ball milling, a second drying, and a second sieving to obtain a pre-treated raw material powder; 3) The pretreated raw material powder obtained in step 2) is pressed into a shape, and then sintered at a low temperature to obtain an ultra-low temperature sintered ceramic material.
6. The preparation method according to claim 5, characterized in that: In the step 1), the particle sizes of the Na source, Ag source, Bi source and Mo source are all 360-400 meshes.
7. The preparation method according to claim 5, characterized in that: In the step 2), deionized water is added so that the raw material powder can be fully dispersed in the water, and then allowed to stand for 15 to 18 hours; And / or, the ball milling speed of the first ball milling is 300-400 rpm, and the ball milling time is 21-24 h; And / or, the first drying temperature is 80-95°C and the drying time is 3-24h; and / or, the sieve for the first screening is 40 to 80 meshes; and / or, the sieve for the second screening is 80 to 110 meshes; And / or, pre-calcining is heating to 325-375°C at a heating rate of 2-5°C / min and pre-calcining for 3.5-4 hours; And / or, the conditions for the second ball milling are the same as those for the first ball milling, and the conditions for the second drying are the same as those for the first drying.
8. The preparation method according to claim 5, characterized in that: In the step 3), the pressing molding is to press the ceramic green body under a pressure of 1 to 3 bar; the low temperature sintering is to sinter the ceramic green body at 400 to 535° C. for 3.5 to 4 hours to obtain the ultra-low temperature sintered ceramic material.
9. The preparation method according to claim 8, characterized in that: The ceramic green body is a cylindrical block with a diameter of 10 to 12 mm and a height of 4 to 6 mm; And / or, before sintering, the ceramic green body is left to stand for 8 to 10 hours.
10. Use of the ultra-low temperature sintered ceramic material according to any one of claims 1 to 4, or the ultra-low temperature sintered ceramic material prepared by the preparation method according to any one of claims 5 to 9 in information communication materials.
Citation Information
Patent Citations
Temperature-stable ultralow dielectric-constant microwave dielectric ceramic Na2ZnMo2O8 and preparation method thereof
CN105272246A
Ultralow-temperature sintered low-dielectric low-loss LTCC material and preparation method thereof
CN113816736A
Low firing ceramic composition for microwavecomponents and manufacture method therefor
KR1020050020355A
Method for controlling a safety door of a battery swap station
KR102655766B1
Cold sintering ceramics and composites
US20170088471A1